Is it Time to Reboot Local Government IT Professionals? Examining Emotional Labor in Local Government IT Professionals - Khan, Jessica F.; Jacobson, Willow S.; Tufts, Shannon H.; Somerville, Hannah L. (Review of public personnel administration, 2025)
The public sector has experienced a significant increase in its reliance on and expectations from the Information Technology (IT) function. This reliance has led to a significant burden placed upon public sector IT professionals to keep up with demand and has inevitably increased the emotional labor burden placed upon these workers. This article examines the extent and types of emotional labor experienced by local government IT professionals and how it has an impact on key workforce outcomes of burnout and job satisfaction. This article examines the impact of emotional labor types and levels on critical indicators of burnout (an increasing concern across the workforce) and employee satisfaction. Both burnout and job satisfaction have been linked to turnover intention and employee performance. This research adds to the empirical work on emotional labor including an analysis focused on the predictive value of emotional labor.